2017
DOI: 10.1177/1363459317693406
|View full text |Cite
|
Sign up to set email alerts
|

To be or not to be sick and tired: Managing the visibility of HIV and HIV-related fatigue

Abstract: This article takes a new direction in exploring HIV-related fatigue by adopting a qualitative interactionist approach. We analyse the social meanings attributed to fatigue among people living with HIV in France, the social gains and losses of its visibility and the social frames that condition its discursive and physical expression. The two-part methodology combines grounded theory analysis of 50 transcribed unstructured interviews conducted across France and participant observations within four HIV-related as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
3
7
0
Order By: Relevance
“…Fatigue is a common and disabling symptom among persons living with HIV (Barroso & Voss, 2013), but little is known about how to assess it among adolescents, particularly in low and middle income countries where rates of HIV in this age group are highest (Joint United Nations Programme on HIV/AIDS [UNAIDS], 2014). Chronic fatigue is a prolonged state of tiredness, exhaustion and lack in energy (Schuft, Duval, Thomas, & Ferez, 2017). It is inherently subjective and as such, is most frequently assessed by self-report e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue is a common and disabling symptom among persons living with HIV (Barroso & Voss, 2013), but little is known about how to assess it among adolescents, particularly in low and middle income countries where rates of HIV in this age group are highest (Joint United Nations Programme on HIV/AIDS [UNAIDS], 2014). Chronic fatigue is a prolonged state of tiredness, exhaustion and lack in energy (Schuft, Duval, Thomas, & Ferez, 2017). It is inherently subjective and as such, is most frequently assessed by self-report e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The mothers become passive in providing care for children [12]. The main factors are physical fatigue of the mothers and psychological burden [29].…”
Section: Tendency Of Authoritarian and Permissive Parenting In Childrenmentioning
confidence: 99%
“…The latter concept considers that people have agency to "choose" to a certain extent how they live with or manage chronic illness. Recent research has suggested that such "choices" as well as the physical experience of HIV are facetted by social contexts of interaction, and an interplay between the sentiment of HIV (in)visibility (Persson 2005;Thomas et al 2014;Alexias et al 2016) and the acceptability of disclosing HIV or physical symptoms (Mackworth-Young, Bond, and Wringe 2020; Schuft et al 2018). These findings suggest that illness narratives are influenced by both physical experiencesregarding the body, treatments or symptomsand social experiences along illness trajectories.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Whether constituting a major "biographical disruption" (Bury 2001) or a "life-event" (Goffman 1963) among social and economic hardships (Ciambrone 2001;McGrath et al 2014;Wouters and Wet 2016), HIV diagnosis entails a certain amount of ongoing adaptations or identity work. These adaptations are in interaction with HIV stigma (Geary et al 2014;Marsicano et al 2014;Smith, Rossetto, and Peterson 2008) and the illness itself, including medical monitoring or the management of symptoms or treatment side effects (Alexias, Savvakis, and Stratopoulou 2016;Schuft et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation